Viral infection in chronic otitis media with effusion in children - Runge, Annette; Straif, Sonja; Banki, Zoltan; Borena, Wegene; Muellauer, Brigitte; Brunner, Juergen; Gottfried, Timo; Schmutzhard, Joachim; Dudas, Jozsef; Risslegger, Brigitte; Randhawa, Avneet; Lass-Flörl, Cornelia; et al. (Frontiers in Pediatrics, 2023)
Background: The role of respiratory viruses in chronic otitis media with effusion (COME) in children is not clearly defined. In our study we aimed to investigate the detection of respiratory viruses in middle ear effusions (MEE) as well as the association with local bacteria, respiratory viruses in the nasopharynx and cellular immune response of children with COME. Methods: This 2017-2019 cross-sectional study included 69 children aged 2-6 undergoing myringotomy for COME. MEE and nasopharyngeal swabs were analysed via PCR and CT-values for the genome and loads of typical respiratory viruses. Immune cell populations and exhaustion markers in MEE related to respiratory virus detection were studied via FACS. Clinical data including the BMI was correlated. Results: Respiratory viruses were detected in MEE of 44 children (64%). Rhinovirus (42%), Parainfluenzavirus (26%) and Bocavirus (10%) were detected most frequently. Average Ct values were 33.6 and 33.5 in MEE and nasopharynx, respectively. Higher detection rates correlated with elevated BMI. Monocyte were elevated in MEE (9.5±7.3%/blood leucocytes). Exhaustion markers were elevated on CD4+ and CD8+ T cells and monocytes in MEE. Conclusion: Respiratory viruses are associated with pediatric COME. Elevated BMI was associated with increased rates of virus associated COME. Changes in cell proportions of innate immunity and expression of exhaustion markers may be related to chronic viral infection.